The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/rs15174157
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Water Quality Parameters through a Combination of Deep Learning and Remote Sensing Techniques in a Lake in Southern Chile

Lien Rodríguez-López,
David Bustos Usta,
Iongel Duran-Llacer
et al.

Abstract: In this study, we combined machine learning and remote sensing techniques to estimate the value of chlorophyll-a concentration in a freshwater ecosystem in the South American continent (lake in Southern Chile). In a previous study, nine artificial intelligence (AI) algorithms were tested to predict water quality data from measurements during monitoring campaigns. In this study, in addition to field data (Case A), meteorological variables (Case B) and satellite data (Case C) were used to predict chlorophyll-a i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 76 publications
1
8
0
Order By: Relevance
“…When comparing the in situ Chl-a and turbidity data to the reflectance signals corrected by the different atmospheric methods, ACOLITE showed the highest coefficients of determination, reaching R 2 values of 0.88 and 0.79 for Chl-a and turbidity, respectively. These results are in line with a recent study conducted by Rodríguez-López et al [9], in which ACOLITE was used as an atmospheric distortion mitigation method on L-8 OLI scenes to estimate Chl-a concentrations in the Llanquihue Lake (Southern Chile). Other water quality research studies have found that ACOLITE effectively corrects for atmospheric distortions in water bodies, especially in the development of Chl-a estimation models from L-8 satellite OLI scenes (e.g., [56][57][58]).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…When comparing the in situ Chl-a and turbidity data to the reflectance signals corrected by the different atmospheric methods, ACOLITE showed the highest coefficients of determination, reaching R 2 values of 0.88 and 0.79 for Chl-a and turbidity, respectively. These results are in line with a recent study conducted by Rodríguez-López et al [9], in which ACOLITE was used as an atmospheric distortion mitigation method on L-8 OLI scenes to estimate Chl-a concentrations in the Llanquihue Lake (Southern Chile). Other water quality research studies have found that ACOLITE effectively corrects for atmospheric distortions in water bodies, especially in the development of Chl-a estimation models from L-8 satellite OLI scenes (e.g., [56][57][58]).…”
Section: Discussionsupporting
confidence: 91%
“…As a result, Equation ( 9) is the final turbidity retrieval model. Turbidity = 0.51 × e (130.75×(Red+N IR)) (9) As in the Chl-a estimation model, the bootstrapping method was performed using 1000 iterations to optimize the selection of function parameters between mean and median (Figure 13). As a result, Equation ( 9) is the final turbidity retrieval model.…”
Section: Statistical Evaluation and Robustness Of The Turbidity Estim...mentioning
confidence: 99%
See 2 more Smart Citations
“…Eutrophication, an essential manifestation of water pollution in freshwater reservoirs, results from the excessive nutrient loads that cause algal blooms [1,2]. The excessive algae and aquatic plant growth result in oxygen depletion, ultimately causing severe impacts on aquatic ecosystems and considerably increasing the costs related to water treatment [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%